2002
DOI: 10.1159/000058453
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma in Long-Standing Untreated Lichen sclerosus et atrophicus of the Penis

Abstract: Lichen sclerosus et atrophicus is an uncommon disease of skin and genital mucosa in both sexes. Involvement of the male genital mucosa is usually complicated by recurrent balanoposthitis, ulceration, phimosis, and meatal stenosis. The development of a squamous cell carcinoma is extremely rare in genital lichen sclerosus et atrophicus in males as compared with females. We report a 70-year-old male with a squamous cell carcinoma of the glans superimposed on long-standing lichen sclerosus et atrophicus of glans a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2003
2003
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…Penile lichen sclerosus (balanitis xerotica obliterans) is a chronic sclerosing inflammatory disorder of unknown cause that may lead in some cases to meatal stenosis or acquired phimosis (Fig 1). 182,[191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210] There have been anecdotal reports of men developing penile SCC 191,203,204 or verrucous carcinoma 172,182 in association with genital lichen sclerosus. Since penile lichen sclerosus often leads to phimosis, it has been suggested that in lichen sclerosuseassociated penile carcinoma, phimosis probably represented a more important carcinogenic factor than lichen sclerosus itself.…”
Section: Lack Of Circumcision and Related Factorsmentioning
confidence: 99%
“…Penile lichen sclerosus (balanitis xerotica obliterans) is a chronic sclerosing inflammatory disorder of unknown cause that may lead in some cases to meatal stenosis or acquired phimosis (Fig 1). 182,[191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210] There have been anecdotal reports of men developing penile SCC 191,203,204 or verrucous carcinoma 172,182 in association with genital lichen sclerosus. Since penile lichen sclerosus often leads to phimosis, it has been suggested that in lichen sclerosuseassociated penile carcinoma, phimosis probably represented a more important carcinogenic factor than lichen sclerosus itself.…”
Section: Lack Of Circumcision and Related Factorsmentioning
confidence: 99%
“…Tel. Moreover, development of penile SCC in LSA is a rare event and seldom reported in the literature (Paricio Rubio et al, 1999;Powell et al, 2001;Kanwar et al, 2002). To our knowledge, this is the first case of SCC pLSA related to HCV infection.…”
Section: Brief Communicationmentioning
confidence: 81%
“…In the literature, about 20 cases of penile carcinoma (SCC, verrucous carcinoma, adenosquamous carcinoma) with histological evidence of LSA are described (Paricio Rubio et al, 1999;Powell et al, 2001;Kanwar et al, 2002). In the literature, about 20 cases of penile carcinoma (SCC, verrucous carcinoma, adenosquamous carcinoma) with histological evidence of LSA are described (Paricio Rubio et al, 1999;Powell et al, 2001;Kanwar et al, 2002).…”
Section: Brief Communicationmentioning
confidence: 99%
“…This association is, however, not so well established in males. In males, the occurrence of malignant changes in penile LSA is extremely rare and has been only sporadically reported (2, 4, 515). The pathogenesis of SCC arising in LSA is unclear.…”
Section: Discussionmentioning
confidence: 99%